Weak correlations between hemodynamic signals and ongoing neural activity during the resting state. (December 2017) - Winder, Aaron; Echagarruga, Christina; Zhang, Qingguang; Drew, Patrick
Abstract Spontaneous fluctuations in hemodynamic signals in the absence of a task or overt stimulation are used to infer neural activity. We tested this coupling by simultaneously measuring neural activity and changes in cerebral blood volume (CBV) in the somatosensory cortex of awake, head-fixed mice during periods of true rest and during whisker stimulation and volitional whisking. We found that neurovascular coupling was similar across states and that large, spontaneous CBV changes in the absence of sensory input were driven by volitional whisker and body movements. Hemodynamic signals during periods of rest were weakly correlated with neural activity. Spontaneous fluctuations in CBV and vessel diameter persisted when local neural spiking and glutamatergic input were blocked, as well as during blockade of noradrenergic receptors, suggesting a non-neuronal origin for spontaneous CBV fluctuations. Spontaneous hemodynamic signals reflect a combination of behavior, local neural activity, and putatively non-neural processes. The relationship of resting-state hemodynamics signals to ongoing neural activity is poorly understood. Using optical imaging, electrophysiology, and local pharmacological infusions, Winder et al. found that resting hemodynamic signals were weakly correlated with neural activity and that these hemodynamic fluctuations persisted when neural activity was silenced.